Los juegos tradicionales y la motricidad gruesa en los niños del nivel inicial II de la Escuela de Educación Básica Rosa Josefina Burneo de Burneo, de la ciudad de Loja, periodo académico 2021-2022. - Riofrio Padilla, Carolina Stephany (2023)
Gross motor skills are focused on generating movements of specific parts of the body that allow the acquisition of abilities and skills such as coordination, balance, to move from one place to another through these, perfecting over time and the necessary stimulation. The present investigation was focused on determining how traditional games improve gross motor skills in children of Initial II, of the Rosa Josefina Burneo de Burneo School of Basic Education, in the city of Loja. There was a mixed approach, descriptive scope, quasi-experimental design and inductive-deductive methods fulfilled the stated objectives, the construction of knowledge and determine the respective conclusions and analytical-synthetic individually analyzed the variables considering the most relevant information of each topic for the construction of the theoretical framework. The techniques and instruments used were an interview with the teacher in order to acquire information about gross motor problems and the strategies that are frequently used for the development of children. As an instrument, the Psychomotor Development test in children from 0 to 5 years of Haeussler and Marchant was used, which allowed knowing the level of gross motor development, showing that 50% of children were at a level of risk and delay. Therefore, an activity guide based on traditional games was applied, which was worked with a value scale to a sample of 13 children, denoting that 71% of children managed to improve gross motor skills. The feasibility of increasing traditional games as a didactic strategy in the development of motor skills that allow children to correctly strengthen their body scheme, coordination and balance is corroborated. Keywords: traditional games, gross motor skills, sports activities, mastery of balance